Laporan Kasus: Radiografi Thorax pada Pasien Tb Paru dengan Pneumothorax Spontan Sekunder - Rian Parsaoran Andreas Simamora; Rasyidah Rasyidah (Majority, 2020)
Pneumothorax is a collection of air and gas contained in the pleural cavity. Pneumothorax is divided into spontaneous (primary and secondary) and traumatic pneumothorax. Secondary spontaneous pneumothorax can occur preceded by underlying disease,as in the case of pulmonary tuberculosis (Tb). The most common manifestations in this case, such as dypsnoe, chest pain, coughing, asymmetrical chest wall, and hypersonor. Case report, a 75 years old man was taken to the hospital complained of dypsnea since 3 weeks before admission, accompanied by coughing with green sputum. The patient complained fever and sweating at night 2 weeks before. Physical examination showed asymmetrical chest movement and shape, right fremitus tactile is lagging, hypersonor in the right hemithorax. Complete blood examination showed leukocytes 15.300/uL and radiographic examination showed an avascular lucency shadow with white pleural line and infiltrates with fibrosis in both lungs, leading to secondary spontaneous pneumothorax ec primary lung tb. Patient were given non-medical therapy with oxygenation and insertion of chest tube, meanwhile medical therapy by administering antibiotic and analgesic.